Formulation and Characterization of Mefenamic Acid Self Nanoemulsifying Drug Delivery System (SNEDDS) Preparations - Farrah Bintang Sabiti; Sukarno (Open Access Indonesian Journal of Medical Reviews, 2024)
Mefenamic acid is included in BCS (biopharmaceutical classification system) class II, namely high permeability and low solubility. This research aims to obtain a good formula for oleic acid oil, tween 80, and PEG 400 according to the characterization test of emulsification time, % transmittance, drug loading, globule size, and zeta potential. This research was an experimental study by formulating mefenamic acid in the form of SNEDDS which was made 1 formula was made in the form of SNEDDS with the composition of oleic acid, tween 80, and PEG 400 and characterization tests were carried out for emulsification time, % transmittance, drug loading, globule size, zeta potential. The yield of the oleic acid formula is 1%, tween 80 is 8%, and PEG 400 is 1%. The emulsification time characterization test resulted in 17 seconds, % transmittance of 97%, drug loading of 179.81 mg, globular size of 85.8 nm and zeta potential of -1.6 mV.